2012
DOI: 10.4103/0970-0358.101286
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cells in the management of chronic wounds

Abstract: Chronic wounds continue to be a major challenge for the medical profession, and plastic surgeons are frequently called in to help in the management of such wounds. Apart from the obvious morbidity to the patient, these problem wounds can be a major drain on the already scarce hospital resources. Sometimes, these chronic wounds can be more taxing than the underlying disease itself. Although many newer methods are available to handle such situations, the role of stem cells in the management of such wounds is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
(94 reference statements)
1
20
0
Order By: Relevance
“…Stem cell therapy has been explored extensively in wound healing . Traumatic wounds, most notably those as a result of burns, are of particular interest to clinicians as these wounds are plagued by slow healing, infection, pain, and hypertrophic scarring .…”
Section: Current Stem Cell Therapy For Wound Healingmentioning
confidence: 99%
“…Stem cell therapy has been explored extensively in wound healing . Traumatic wounds, most notably those as a result of burns, are of particular interest to clinicians as these wounds are plagued by slow healing, infection, pain, and hypertrophic scarring .…”
Section: Current Stem Cell Therapy For Wound Healingmentioning
confidence: 99%
“…Also, Sharma and John [32], indicated that the cell membranes release strong vasoconstrictors such as prostaglandin 2 alpha and thromboxane A2 immediately after the acute injury. The collagen in the wound began the cascade of the clotting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sharma and John [32] stated that fibroblasts were stimulated by platelet derived growth factor [PDGF] secreted from platelets and macrophages that existed in the wound. After stimulation, fibroblasts laid down a provisional matrix composed of type III collagen, glycosaminoglycans and fibronectin.…”
Section: Immunohistochemicalmentioning
confidence: 99%
“…28 Chitosan can also stimulate PMN cells to chemotaxyize the wound area due to the presence of IL-1, TNF-α, and bacterial products. 29 In other words, spirulina and chitosan exert a synergistic effect when combined since chitosan plays a role in drug delivery, while spirulina has a therapeutic effect. Spirulina and chitosan can also interact intermolecularly to increase mechanical resistance.…”
Section: Discussionmentioning
confidence: 99%